ALLIGATOR BREEDING IN CAPTIVITY - de Lima, Izabela Maria Santos; Roder, Julio Cesar; de Oliveira, Vanilza Aparecida Alves; Cardoso, Ronaldo; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2023)
The creation of alligators in captivity is a way of preserving the species because the animal in captivity has a longer life expectancy, compared to the animal I have lived in nature. Brazil has great potential for this biobusiness due to its territorial and climatic extensions. The demand for the meat has been increasing due to its nutritional characteristics, low in saturated fat, few calories and free of carbohydrates, for this reason alligator meat is increasingly sought after by consumers looking for healthy eating options. , allied to this the high value of the skin in the foreign market, and the trade of by-products; makes alligator breeding in captivity considered as a potential income option for producers. This study aims to describe the main activities, bringing guidelines on the creation, structure, market analysis and financial viability, done through a bibliographical review, evaluating in a qualitative way. aiming to contribute to new research for this promising field.